2016
DOI: 10.4081/jlimnol.2016.1400
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lake restoration by the hypolimnetic withdrawal method on the intensity of ambient odour

Abstract: The objective of this study was to evaluate the effect of lake restoration by the hypolimnetic withdrawal method on the intensity of ambient odour in the vicinity of the pipeline outlet. The study was carried out in [2012][2013] -N), total nitrogen (TN), dissolved nitrogen (DN), total particulate nitrogen (T-PN), total organic carbon (TOC), dissolved organic carbon (DOC) and total particulate organic carbon (T-POC). Water samples were also analysed to determine total bacterial abundance (TBA) and the counts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The occurrence of hydrogen sulphide is linked with decreased oxygen contents in the water. As Tandyrak et al (2016) demonstrated, these two parameters were significantly, inversely correlated in the Kortówka River. The occurrence of hydrogen sulphide in the waters of the studied river could have come from the deoxygenated, deep layers of the lake.…”
Section: Environmental Parameters and Their Impact On Zooplanktonmentioning
confidence: 74%
See 3 more Smart Citations
“…The occurrence of hydrogen sulphide is linked with decreased oxygen contents in the water. As Tandyrak et al (2016) demonstrated, these two parameters were significantly, inversely correlated in the Kortówka River. The occurrence of hydrogen sulphide in the waters of the studied river could have come from the deoxygenated, deep layers of the lake.…”
Section: Environmental Parameters and Their Impact On Zooplanktonmentioning
confidence: 74%
“…Differences in zooplankton abundance resulted from the fact that in the 1980s the water discharged into the river was mainly from the hypolimnion, which was less rich in zooplankton than was the lake surface water layer. Modifications to pipeline operation include shortening its operating time in the summer-fall period while simultaneously increasing the percentage share of the surface layer waters in the outflow (Dunalska et al, 2007;Tandyrak et al, 2016), thus minimizing the negative ecological impact of lake restoration that is based on reducing zooplankton abundance. This is how lake restoration is made more sustainable in terms of its environmental impact.…”
Section: Coefficientsmentioning
confidence: 99%
See 2 more Smart Citations
“…TSI allows determining the fertility of the lake, which is directly connected with the occurrence of algal blooms (and chlorophyll a content in algae) and consequently, the transparency of the water (SD). The presence of algal blooms, especially cyanobacteria, periodically eliminates a bathing function of reservoir because of the toxic metabolic products of these organisms released into the water (Codd 1995, Tandyrak et al 2016. The presence of cyanobacterial is related to the ratio of TN/TP, the high value of this ratio is favourable, indicating the disappearance of cyanobacterial blooms and the growth of more desirable species.…”
Section: Methodsmentioning
confidence: 99%